2022
DOI: 10.5937/nabepo27-36389
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Serbian version of mental toughness Inventory and Dark Triad Dirty Dozen in police students

Abstract: Police work is a stressful occupation, where officers are exposed to chronic and intense stressors. When it comes to understanding and predicting reaction to prolonged stress, it has been shown that there is more to personality than what can be captured by the most widespread personality models. Adding Mental Toughness as the capacity to tolerate and overcome stress at work, as well as the Dark Triad as a tendency for malevolent behaviour, to the traditional model of assessing the personality of a police offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…According to reliability parameters (Table 2) DTDD shoved excellent properties. This finding is in line with finding of previous validation studies [24], and more over online version shoved greater reliability than paper version in some earlier studies [25]. On the other hand, IRI was quite questionable when it comes to reliability.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to reliability parameters (Table 2) DTDD shoved excellent properties. This finding is in line with finding of previous validation studies [24], and more over online version shoved greater reliability than paper version in some earlier studies [25]. On the other hand, IRI was quite questionable when it comes to reliability.…”
Section: Discussionsupporting
confidence: 92%
“…Results of correlation analyses (Table 3) are also in line with results of previous studies [28,5,26,25,27]. Having in mind direction, intensity, and number of obtained correlations it can be easily claimed that construct validity of online versions of all three instruments in population of basketball players is confirmed.…”
Section: Discussionsupporting
confidence: 88%
“…Never the less, if taken into account the relationship between the size of Cronbach's alpha scores and the number of scales that make up one score, it can be clearly observed that all three instruments behave in a good way according to this parameter. Also, the obtained reliability of the online version of the questionnaire is quite similar to that obtained in the validation studies of the paper versions [18,19,9,20,21,22].…”
Section: Discussionsupporting
confidence: 79%
“…In the end, this study for the subject of analysis had the psychometric properties of online versions of already validated instruments, which are in widely used in sports and research practice. Taking everything into account, the online tests showed at least the same psychometric characteristics as the paper versions [6,9,18,22,19,21,20].…”
Section: Discussionmentioning
confidence: 82%